2023
DOI: 10.1002/edm2.432
|View full text |Cite
|
Sign up to set email alerts
|

The interplay between vitamin C and thyroid

Bahareh Farasati Far,
Amir Hossein Behnoush,
Elina Ghondaghsaz
et al.

Abstract: Vitamin C is involved in the maintenance of several body functions, and its role has been shown in several organs and systems. 1 Although its main form in the body is ascorbate, it acts as a co-substrate for several enzymes and antioxidants. 2,3 Its role as an antioxidant is well known and it is well known as reactive oxygen species (ROS) scavenger in neurons. 4,5 Its concentration in body fluids and tissues depends on intestinal absorption, cellular transport and excretion. 6 The thyroid gland, as one of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 79 publications
0
3
0
Order By: Relevance
“…Vitamin C has multiple benefits for several diseases. In a review, vitamin C was reported to increase the death of cancerous cells by inhibiting BCL-2(B-cell lymphoma-2) expression and increasing the expression of BAX (BCL2-Association X) and caspase-3 18 . A cross-sectional study involving 5145 participants showed an inverse association between vitamin C intake and periodontitis 19 .…”
Section: Discussionmentioning
confidence: 99%
“…Vitamin C has multiple benefits for several diseases. In a review, vitamin C was reported to increase the death of cancerous cells by inhibiting BCL-2(B-cell lymphoma-2) expression and increasing the expression of BAX (BCL2-Association X) and caspase-3 18 . A cross-sectional study involving 5145 participants showed an inverse association between vitamin C intake and periodontitis 19 .…”
Section: Discussionmentioning
confidence: 99%
“…Studies on primary cultures of orbital fibroblasts from TAO patients have shown that vitamin C, N-acetylcysteine and melatonin reduce H 2 O 2 -stimulated glutathione disulphide (GSSG) release, potentially benefiting orbital lesion treatment ( 130 ). Additionally, vitamin C and E supplementation improved clinical symptoms and clinical scores in TAO patients by reducing oxidative stress markers ( 131 ). These antioxidants inhibit TAO fibroblast proliferation, with N-acetylcysteine and melatonin selectively blocking IFN-γ release ( 132 ).…”
Section: Therapeutic Agents For Oxidative Stress In Tao and Their Pot...mentioning
confidence: 99%
“…Vitamins C and E have a strong ability to regulate REDOX. Studies have shown that vitamins C and E can improve oxidative damage in patients with thyroid diseases ( 8 , 9 ). In 1994, Berg discovered the expression of vitamin D receptors on thyroid follicular cells in rats, suggesting that vitamin D may be involved in the pathophysiological processes of the thyroid ( 10 ).…”
Section: Introductionmentioning
confidence: 99%